(untitled) (Research, Society and Development, 2020)
Plosokuning Mosque is the mosque with the most authenticity preserved compared to the other four Pathok Negoro mosques. Therefore, the disclosure of the symbolic value of the architectural aesthetic of the Plosokuning Mosque is a representation of environmental conservation efforts and historical buildings in Indonesia. The research method used was hermeneutics-philosophical with methodical elements: induction-deduction, internal coherence, holistic, historical balance, and heuristics. The methodical elements examined the architecture aesthetical meaning and the symbols attached to Plosokuning Mosque; in line with it, internal relations was searched and discovered, not isolated from the environment and its historical continuity, and then compiled findings about symbolism in the aesthetics of the mosque’s architecture. The results showed that symbolism in the architectural aesthetics of the Plosokuning Mosque is an expression of the concept of Javanese cosmology and Javanese Islamic mysticism (Kejawen). In Javanese cosmology, humans are described as a microcosm (jagad cilik), the universe as a macrocosm (jagad gedhe), and the palace as the center of the cosmos. Kejawen is a complex of Javanese Islamic beliefs mixed with previous teachings, particularly Hindu and Buddhist teachings; The Plosokuning Mosque has elements that are integrated together as a symbol of the means for human contemplation towards insan kamil (perfect human). Thus, the top position of human being is makrifatullah (knowing Allah). It can be concluded that the aesthetic architectural related to the religion matter.